Use of Textbooks in Implementing the Independent Curriculum in High Schools - Hutabarat, Mikael; Banjarahor, Fonti Fai; Sitohang, Jhon Roger; Sagala, Reni; Manullang, Bonita; Tamba, Anggreni; Prasasti, Tri Indah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The aim of this research is to analyze the use of textbooks in the Merdeka curriculum as a new curriculum implemented in schools in Indonesia, especially high schools. Seeing the way students learn in implementing the Merdeka curriculum is more directed towards student exploration, making the use of books less of a priority in this curriculum. So in this journal we will see whether the use of textbooks is still needed or not in the Merdeka curriculum. The method used in this research activity is using descriptive qualitative research methods. And data collection in carrying out this research was by conducting observations and interviews with high schools. And the research results of this research are presented in summary form.